Kejohanan sukan antara fakulti (SAF) 2023 / Syafiqah Saadon, Muhamad 'Izzuddin Zamery and Dr. John Shia Kwong Siew - Saadon, Syafiqah; Zamery, Muhamad 'Izzuddin; John Shia, Kwong Siew (Faculty of Pharmacy, 2023)
The Inter-faculty Sports Tournament (Kejohanan Sukan Antara Fakulti) was conducted on 6th to 22nd January 2023 at UiTM Shah Alam Sports Centre and various locations around the campus. Organised by the Sports Unit, Division of Students Affairs, UiTM Shah Alam, the tournament was participated by 6959 athletes from four uitm campuses namely UiTM Puncak Alam, Puncak Perdana, Dengkil and Sungai Buloh. On this occasion, the Faculty of Pharmacy has sent a total of 318 athletes to compete in 23 sports, including physical and online games.